Seeking Knowledge: The Role of Social Networks in the Adoption of eBooks by Historians - Martin, Kim; Quan-Haase, Anabel (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
This article explores adoption rates of the Ebook amongst Historians at the University of Western Ontario. Employing the first stage of Rogers’ Innovation-Decision Process, the researchers examine the role that social networks play in this process and what effect the Historians’ desire for the possibility of serendipity has on electronic research. Cet article explore le taux d’adoption des livres numériques chez les historiens à l’Université Western Ontario. À l’aide du premier stade du processus innovation-décision de Rogers, on examine le rôle des réseaux sociaux dans ce processus ainsi que les effets sur la recherche électronique qu’a le désir des historiens à s’ouvrir à la serendipité.